2017
DOI: 10.18203/2320-6012.ijrms20175708
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the knowledge and awareness about glaucoma in glaucoma patients and general population: a sample from Turkey

Abstract: Background: The study aimed to evaluate the level of knowledge and awareness of glaucoma and their possible determinants in a group of people diagnosed with glaucoma and in a population based group without glaucoma.Methods: The study included people with an age range of 40 to 80years; 410 patients without glaucoma who admitted to primary health care service and 113 patients who admitted to hospitals with diagnosis of glaucoma. In addition to Glaucoma Knowledge Level Questionnaire (GKLQ), participants were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…It was also reported in the same study that there was no relation of knowledge with the education status, which contradicts our findings. In Turkey the results were similar to our study in which understanding about the ocular diseases was low in people of lower educational status 7 . In a recent research in Egypt, educational status was found positively related with the knowledge about ocular diseases 8 .…”
Section: Discussionsupporting
confidence: 89%
“…It was also reported in the same study that there was no relation of knowledge with the education status, which contradicts our findings. In Turkey the results were similar to our study in which understanding about the ocular diseases was low in people of lower educational status 7 . In a recent research in Egypt, educational status was found positively related with the knowledge about ocular diseases 8 .…”
Section: Discussionsupporting
confidence: 89%
“…This was supported by other studies [13,18,21,26]. People with a high level of education are more likely to attend health education programs, understand the written and visual documents and approach to the information sources which build-up knowledge [28].…”
Section: Discussionsupporting
confidence: 72%
“…This might be due to the difference in study subjects; in the present study, 25.5% of participants were older than 40 years compared to 15.7% in the latter study. Hence, the age-related nature of the disease might contribute to a better knowledge of aged participants which was supported by different studies [22,27,28].…”
Section: Discussionmentioning
confidence: 83%
“…Poor health seeking habits may als associated with educational level and awareness [14,15]. It is known that the higher the educational status, the better health seeking behavior.…”
Section: Resultsmentioning
confidence: 99%